(untitled) (World of finance, 2019)
Introduction. The socio-economic development of Ukraine depends, among other things, on effective housing policies. The existing living conditions of the population require their improvement, and the low level of real incomes does not create the conditions for this. At the same time, the complexity of the mechanism of functioning of the residential real estate market requires the development of an effective housing policy, one of the directions of which is the optimization of sources of housing construction and further development of the legal framework for housing construction in Ukraine. The purpose of the article is to systematize forms and methods of financing housing construction, as well as identification of their advantages and disadvantages. Results. The results of the study have shown that an important condition for the development of the housing market in Ukraine is the availability of sufficient financial resources for developers to provide the necessary volume of construction of residential real estate. The systematization of financing methods has made it possible to identify those that are appropriate to apply in the housing construction process. These include: self-financing, credit financing, unit financing, budget financing, mixed financing. The advantages and disadvantages of using each of the methods of financing in the field of housing construction are substantiated. It is established that the most appropriate forms of housing finance are the following: retained earnings; accumulated reserves; issue of ordinary and preferred shares; bond loan; bank loan; mortgage lending; direct public financing; public-private partnership. Conclusions. Summarizing the above, it can be argued that when deciding on the method and form of housing financing, it is necessary to consider the advantages and disadvantages of each available financing instrument in each individual case of construction of a residential property.